Investigating the correlation between organizational ethics and professional ethics with job burnout and organizational commitment: a cross-sectional study in the nursing staff - Khanian, Azam; Homayuni, Atefeh; Jamshidian, Zakiyeh; Salehi, Azadeh (BMC nursing, 2024)
Adherence to ethical principles and standards in all health professions, especially in the nursing, can have positive outcomes. This study was conducted with the aim of investigating the correlation between organizational ethics and professional ethics with organizational commitment and job burnout in nursing staff. This cross-sectional study was conducted on the nurses working in Shahid Montazeri hospital in Najafabad city. Participants were selected by census method. An online questionnaire was used to collect the data, which consisted of demographic information, Hunt et al.'s organizational ethics questionnaire, Petty's professional ethics inventory, Maslach and Jackson's job burnout questionnaire and Allen and Mayer's organizational commitment questionnaire. Data were analyzed using t-test, one-way analysis of variance, Pearson correlation coefficient and structural equation modeling (SEM) with SPSS-27 and Amos-23 statistical software. A total of 197 subjects with the mean age of 34.67 ± 7.74 years participated in this study. Most of the participants were female (89.3%) and married (77.2%). The majority of them had a bachelor's degree (86.3%) and 61.4% of the participants participated as a nurse. There were significant positive correlations between organizational ethics (r = 0.551, p < 0.01) and professional ethics (r = 0.44, p < 0.01) with organizational commitment. Also, there were significant negative correlations between organizational ethics (r=-0.532, p < 0.01) and professional ethics (r=-0.602, p < 0.01) with job burnout. Considering the importance of compliance with ethics in the workplace by nursing staff and its consequences such as increasing organizational commitment and reducing job burnout, it is suggested that hospital managers emphasize the compliance with ethics in the workplace as a model. They can also familiarize nursing staff with the principles and basics of organizational and professional ethics by holding training courses.